2009
DOI: 10.1021/jf900041j
|View full text |Cite
|
Sign up to set email alerts
|

Functional Proteomic Analysis Predicts Beef Tenderness and the Tenderness Differential

Abstract: Inconsistent tenderness is one of the most detrimental factors of meat quality. Functional proteomics was used to associate electrophoretic bands from the myofibrillar muscle fraction to meat tenderness in an effort to gain understanding of the mechanisms controlling tenderness. The myofibrillar muscle fraction of the Longissimus dorsi from 22 Angus cross steers was analyzed by SDS-PAGE and linearly regressed to Warner-Bratzler shear values. Six significant electrophoretic bands were characterized by electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
71
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 40 publications
12
71
0
2
Order By: Relevance
“…The finding coincides with the lower pH and higher Note: a, b means within a row with different superscripts are significantly different at P < 0.05 Nota: a, b los promedios en una misma fila con diferente superíndice son significativamente distintos a P < 0,05 tenderness in gas-stunned birds compared with their Halal counterparts. In line with the current finding, increased expression of creatine kinase has been associated with increased meat tenderness in cows (Bjarnadóttir et al, 2012;Zapata, Zerby, & Wick, 2009). Gas stunning up-regulated (P < 0.05) pyruvate kinase isozyme.…”
Section: Muscle Proteomesupporting
confidence: 90%
“…The finding coincides with the lower pH and higher Note: a, b means within a row with different superscripts are significantly different at P < 0.05 Nota: a, b los promedios en una misma fila con diferente superíndice son significativamente distintos a P < 0,05 tenderness in gas-stunned birds compared with their Halal counterparts. In line with the current finding, increased expression of creatine kinase has been associated with increased meat tenderness in cows (Bjarnadóttir et al, 2012;Zapata, Zerby, & Wick, 2009). Gas stunning up-regulated (P < 0.05) pyruvate kinase isozyme.…”
Section: Muscle Proteomesupporting
confidence: 90%
“…This suggests an early proteolysis, which can be explained by lower pH thus promoting the activity of proteases. Bands whose molecular weight is in the order of: 13,14,16,18,23,26,33,36, 42 and 53kDa, persisted in the electrophoretic profile of refrigerated muscles or having previously been treated by one organic acid solutions used, between 24 hours and 48 hours postmortem. Intensity was more remarkable at the end of the experiment (48 hours) (Figure 2).…”
Section: IIImentioning
confidence: 99%
“…RESULTS AND DISCUSSION According to Jia et al, [17]; Zapata et al, [18]; Kemp et al, [19] and Ouali et al, [20], post-mortem maturation of muscles is an enzymatic process that leads to degradation of myofibrillar structures and to lesser extent collagens by endogenous proteolytic enzymes, which will condition tenderizing red meat. Proteolysis of the myofibrillar proteins was evaluated in the LD muscle preserved by refrigeration or treated with citric acid or 1% lactic acid 4% before being refrigerated.…”
Section: IIImentioning
confidence: 99%
See 1 more Smart Citation
“…Laville et al (2009) examined proteomic changes during meat aging in tough and tender beef using 2-DE and found that a higher proportion of proteins from the inner and outer membrane of mitochondria were found in the tender group, suggesting that a more extensive degradation of this organelle may be related to the apoptotic process. In another study into relationships between the protein composition of myofibrillar beef muscle proteins and tenderness Zapata et al (2009) analysed by 1-DE and nano-LC-MS/MS the myofibrillar muscle fraction of longissimus dorsi from 22 Angus cross steers that had linearly regressed to shear values. Six bands showed a significant relationship and were found to contain a wide variety of cellular pathways involving structural, metabolic, chaperone and developmental functions.…”
Section: Meatmentioning
confidence: 99%